Time course of neuromuscular changes during running in well-trained subjects - Ross, E. Z.; Goodall, S.; Stevens, A.; Harris, I. (Medicine & Science in Sports & Exercise, 2010)
Purpose: Prolonged exercise reduces the capacity of the neuromuscular system to produce force, which is known as fatigue. The purpose of this study was to examine the time course of neural and contractile processes during a 20-km running bout.